STRATEGI DAKWAH KEMENAG DALAM PEMBINAAN PEMAHAMAN ISLAM PADA WARGA BINAAN LAPAS IIB KOTA BLITAR - Athoillah, Lizamul Firdaus; Slamet, Moh. (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2024)
This article discusses the da'wah strategies implemented by the Ministry of Religious Affairs to develop Islamic understanding among inmates at Class IIB Penitentiary in Blitar City. The purpose of this research is to describe how the Ministry of Religious Affairs approaches and interacts with inmates to enhance their understanding of Islamic teachings. This research uses a qualitative approach with data collection techniques including interviews, observations, and analysis of related documents. Participants in this study consist of Ministry of Religious Affairs officials and several inmates involved in the da'wah program at the penitentiary. The results of the study show that the Ministry of Religious Affairs employs several da'wah strategies, such as organizing lectures, spiritual guidance, and other religious activities to provide better religious understanding to inmates. Additionally, they also implement a personal approach and focus on strengthening religious values to shape better character.